Grounds for the necessity of fuel supply regulation of the high-pressure pump in the accumulator fuel system - Pozhydaiev, Ivan (National Technical University "Kharkiv Polytechnic Institute", 2025)
The article focuses on promising approaches to regulating the performance of a high-pressure fuel pump (HPFP) for a Common Rail (CR) fuel system. A design concept for the HPFP, which includes an electronic regulator (actuator) for controlling fuel supply, is proposed.
Keywords: diesel engine; diesel fuel system; accumulator fuel system; high pressure fuel pump; power losses